Systematic review of herbals as potential anti-infl ammatory agents: Recent advances, current clinical status and future perspectives - Beg, Sarwar; Swain, Suryakanta; Hasan, Hameed; Barkat, M Abul; Hussain, Md Sarfaraz (Pharmacognosy Reviews, 2011)
Many synthetic drugs reported to be used for the treatment of inflammatory disorders are of least interest now a days due to their potential side effects and serious adverse effects and as they are found to be highly unsafe for human assistance. Since the last few decades, herbal drugs have regained their popularity in treatment against several human ailments. Herbals containing anti-inflammatory activity (AIA) are topics of immense interest due to the absence of several problems in them, which are associated with synthetic preparations. The primary objective of this review is to provide a deep overview of the recently explored anti-inflammatory agents belonging to various classes of phytoconstituents like alkaloids, glycosides, terpenoids, steroids, polyphenolic compounds, and also the compounds isolated from plants of marine origin, algae and fungi. Also, it enlists a distended view on potential interactions between herbals and synthetic preparations, related adverse effects and clinical trials done on herbals for exploring their AIA. The basic aim of this review is to give updated knowledge regarding plants which will be valuable for the scientists working in the field of anti-inflammatory natural chemistry.
Keywords: Alkaloids; anti-inflammatory agents; cannabinoids; clinical trials; glycosides; herbals; inflammation